Correlation between transient evolutions of the gate and drain currents in AlGaN/GaN technologies. Issue 9 (August 2015) - Lazăr, O.; Tartarin, J.G.; Lambert, B.; Moreau, C.; Roux, J.L.
Abstract: This work focuses on short term and long term time evolution of charges in the context of early identification of failure mechanisms in AlGaN/GaN High Electron Mobility Transistors (HEMTs). High power and high frequency devices are needed for new microwave applications, and large band-gap HEMTs offer a powerful alternative to traditional technologies (Si, GaAs, SiGe etc.); however, reliability issues still hamper the potential of these technologies to push their limits in terms of mean time to failure or junction temperature. This paper contributes to the investigation of transient behaviors of gate and drain currents over a large time scale for gallium nitride HEMTs; a correlation is found between the currents' evolution, in spite of the non-monotonic behavior, and a model is given through a mathematical relationship. Charges under the gated zone of the transistor are found to evolve with time, and turn into command variations of the electron density in the 2DEG. This work addresses the consequences of charge dependent mechanisms on the drain current's drop, and thus of the output power. Highlights: Transient variations on the gate and drain currents are correlated. The two currents evolve according to time dependent charges. Charges are located in the gated zone and act as an intrinsic generator. A mathematical model is used to compare leaky and non-leaky devices' behaviors. The method can help to anticipate short and long term memory effects in circuits.